Epidemiological characteristics for patients with traumatic brain injury and the nomogram model for poor prognosis: an 18-year hospital-based study - Guo, Shaochun; Han, Ruili; Chen, Fan; Ji, Peigang; Liu, Jinghui; Zhai, Yulong; Chao, Min; Zhao, Wenjian; Jiao, Yang; Fan, Chao; Huang, Tao; Wang, Na; et al. (Frontiers in Neurology, 2023)
In the context of rapid development of urbanization, the analysis of TBI rate and mortality trend could provide abundant diagnosis and treatment suggestions, which helps to form future reference on public health strategies. In this study, as one of major neurosurgical centers in China, we focused on the regime shift of TBI based on 18-year consecutive clinical data and evaluated the epidemiological features. In our current study, a total of 11,068 TBI patients were reviewed. Overall, male patients (n=8529 [77.06%]) were more likely to be injured, with a median age of onset of 43 years (IQR 25-56), The major cause of TBI was road traffic injuries (RTI) (44.46%), while the main type of injury was cerebral contusion (n=4974 [44.94%]). Regarding to temporal changes, an increasing trend for those aged over 45 years was indicated, especially, the increase was most pronounced in patients over 65 years of age. Incidences of RTI and assaults decreased, while ground level fall (GLF) presented increasing incidences. The total number of deaths was 933 (8.43%), with a decreasing trend in overall mortality since 2011. Age, cause of injury, GCS at admission, Injury Severity Score (ISS), shock state at admission, trauma-related diagnoses and treatments were significantly associated with mortality. A predictive nomogram model for poor prognosis was developed based on patient's GOS scores at discharge, and the calibration curve for this predictive model showed good agreement (internal validation showed a C-statistic of 93.04% (95% CI: 92.3–93.70) for the risk score. The external validation cohort showed good agreement with an accuracy of 81.02% (95% CI: 80.3–82.70). The trends and characteristics of TBI patients changed with rapid development of urbanization in the past 18 years. Further larger studies are warranted to verify its clinical suggestions.